HLA class II association with autoimmune hepatitis in Latin America: A meta-analysis (2009)
Background: Autoimmune hepatitis (AIH) is a chronic liver disease to which different Human Leukocyte Antigens (HLA) have been associated, according to the ethnic/geographical group affected, age of presentation, prognosis, and serologic profile. Objective: To identify common HLA class II alleles contributing to susceptibility to AIH in Latin American population. Methods: The present study was held through a systematic review of the literature, followed by a meta-analysis of 694 cases and 1769 controls of all case-control studies that supplied enough information for odd ratio and 95% confidence interval calculation conducted to date in Latin America. Results: The serological group DQ2 was found to be risk factor for AIH, while DR5 and DQ3 were found to be protective factors in this population. At the allelic level, DQB1*02, DQB1*0603, DRB1*0405, and DRB1*1301, were found to be risk factors, while DRB1*1302 and DQB1*0301 alleles were protective factors. The physicochemical similarities and differences of critical amino acids encoding the peptide binding groove at pockets P1, P4, and P6 of these HLA molecules, elucidates their influence in the development of disease. Conclusion: The current study strengthens the HLA component of AIH in Latin America and its relationship to other populations around the world. © 2008 Elsevier B.V. All rights reserved.